ANALYSIS OF THE IMPLEMENTATION OF WEB-BASED MANAGEMENT INFORMATION SYSTEMS AS A SOLUTION TO DIGITIZE ADMINISTRATION IN EDUCATIONAL INSTITUTIONS - Mauizatul Hasanah; Misjelina Br Surbakti; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The increasing importance of school administration digitization to improve efficiency, transparency and quality of educational services. Web-based Management Information systems (MIS) offer strategic solutions for managing all institute administration data and processes in an integrated and real time manner. This study aims to analyze the literature on the implementation of web-based MIS in educational institutions. To achieve this study conducts a literature review by examining relevant research findings to provide a comprehensive overview of the benefits, challenges and success factors of implementing web-based MIS in the education sector. the review indicates that web-based MIS facilitates the digitalization of school administration, provides all stakeholders with more information, and aids in faster and more accurate decision-making. However, several obstacles such as network infrastructure, human resources and socialization remain major challenges that need to be overcome (Fatoni et al., 2025).